Innovation Dynamics of EU Regions in the Period 1999–2008 - Markowska, Małgorzata (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The study presents approaches to measuring regional innovation and the selection of characteristics facilitating the illustration of this phenomenon at the NUTS 2 level in the EU following dynamic analysis. The research procedure is described, allowing for the classification to be used in the assessment of innovation dynamics. Based on this classification, the results were characterised with a particular emphasis on the territorial distribution of the classes of regions and assigning Polish and capital regions to the obtained classes of innovation dynamics.